Impact of Income Levels and Residential Concerns among China's Migrating Population: An empirical analysis based on urbanization - Li, Kexuan (International Journal of Global Economics and Management, 2024)
This paper utilizes data from the China Migrant Dynamic Survey (CMDS) to empirically analyze the relationship between the income level of migrants in their destination cities and their attention to changes in their place of residence. The regression results of the logit model indicate that an increase in income level significantly enhances individuals' attention to changes in their place of residence. This paper also employs robustness checks and heterogeneity analysis, and the conclusions are consistent with the baseline regression results, supporting the hypothesis that income level has a positive impact on attention to place of residence. The paper also uses entropy balancing matching methods to address potential endogeneity issues that may affect the robustness of the conclusions, reducing the impact of sample selection bias, two-way causality, and omitted variables, thereby enhancing the robustness of the analysis results and the accuracy of causal inference. Heterogeneity analysis results show that the impact of income on different groups is significantly different. Particularly, high-income males, individuals with low education levels, and those with agricultural household registrations are more sensitive to changes in their place of residence, indicating that these groups have higher adaptation needs and attention when facing urban changes.